Nghiên cứu tổng hợp và đặc trưng xúc tác MgO, Co/SiO2 trong phản ứng Fischer-Tropsch ở áp suất thường - An, Vũ; Sơn, Lê Thái; Phương, Trần Thanh; Tùy, Đào Quốc; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2015)
The catalyst samples MgO, 25 %Co/SiO2 with different content of  MgO have been prepared by incipient wetness impregnation method using Mg(NO3)2 solution and 25 %Co/SiO2 support. The catalyst was characterized by XRD, BET, TPD CO and TPR-H2 methods and atalytic activity was determined by Fischer-Tropsch synthesis reaction at ambient pressure. The obtained results show that the catalyst has the highest metal dispersal degree and reaction over this catalyst gave a higher C5+ product distribution than that of  25 %Co/SiO2.